"Making our job hospitable" - Assessment of job-crafting behavior among dental academic faculty in South India - V Siva Kalyan; S Manjula; Chaitanya Kondeti; T Madhavi Padma; S Suresh; K V. N. R. Pratap (Wolters Kluwer Medknow Publications, 2018)
Introduction: Employees are regularly offered opportunities to make their work more appealing and rewarding. These opportunities might be as simple as making fine changes to their daily tasks to boost happiness and to connect with more people at vocation. Hence, an attempt is made to assess job-crafting behavior among the dental academic faculty. Materials and Methods: A cross-sectional study was conducted among dental academic faculty from five dental colleges. Job Crafting Questionnaire (JCQ) was used to assess the job-crafting behavior. Mean scores were calculated for different domains of JCQ. Gender differences were analyzed using Student's "t-" test and one-way ANOVA to test the difference between different academic positions of the faculty members. Results: A total of 228 dental faculty members with a mean age of 34.43 ± 6.13 years participated in the study. The mean value of job-crafting behavior was found to be highest among female faculty (60.07 ± 8.38) and professors (61.35 ± 8.30). Male faculty scored higher in task-crafting domain and female faculty scored higher in both cognitive- and relational-crafting domains. The professors scored highest in all the three domains of job-crafting behavior as compared to that of senior lecturers and readers. Conclusion: Job crafting is an effectual workplace intervention, where employees assume an active role in shaping their work experience to enhance their job satisfaction and well-being. The overall score of job-crafting behavior was found to be highest among both professors and female faculty members. Male faculty members scored higher in task-crafting domain. With regard to individual domains, the participants scored highest in cognitive crafting followed by task and relational crafting.